Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(3\frac{1}{2}-\frac{1}{2}.\left(-4,25-\frac{3}{4}\right)^2:\frac{5}{4}\)
\(=\frac{7}{2}-\frac{1}{2}.\left(-4,25-0,75\right)^2:\frac{5}{4}\)
\(=\frac{7}{2}-\frac{1}{2}.\left(-5\right)^2:\frac{5}{4}\)
\(=\frac{7}{2}-\frac{1}{2}.5.\frac{4}{5}\)
\(=\frac{7}{2}-2\)
\(=\frac{7}{2}-\frac{4}{2}\)
\(=\frac{3}{2}\)
\(\frac{3}{7}.1\frac{1}{2}+\frac{3}{7}.0,5-\frac{3}{7}.9\)
\(=\frac{3}{7}.\left(\frac{3}{2}+\frac{1}{2}-9\right)\)
\(=\frac{3}{7}.\left(2-9\right)\)
\(=\frac{3}{7}.\left(-7\right)\)
\(=-3\)
\(\frac{125^{2016}.8^{2017}}{50^{2017}.20^{2018}}=\frac{\left(5^3\right)^{2016}.\left(2^3\right)^{2017}}{\left(5^2\right)^{2017}.2^{2017}.\left(2^2\right)^{2018}.5^{2018}}=\frac{\left(5^3\right)^{2016}.\left(2^3\right)^{2017}}{\left(5^3\right)^{2017}.\left(2^3\right)^{2017}.2.5}=\frac{1}{5^4.2}=\frac{1}{1250}\)( tính nhẩm, ko chắc đúng )
1
a) \(3\frac{1}{2}-\frac{1}{2}\cdot\left(-4,25-\frac{3}{4}\right)^2\) : \(\frac{5}{4}\)
= \(3\cdot25:\frac{5}{4}\)
= \(3\cdot\left(25:\frac{5}{4}\right)\)
=\(3\cdot20\)
=60
b)=\(\frac{3}{7}\cdot\left(1\frac{1}{2}+0,5-9\right)\)
=\(\frac{3}{7}\cdot\left(-7\right)\)
=\(-3\)
c) =
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1 :
a. \(\left|x-\frac{1}{3}\right|< \frac{5}{2}\)
TH1 : nếu \(\left|x-\frac{1}{3}\right|>0\)
\(x-\frac{1}{3}< \frac{5}{3}\)
\(x< 2\)
TH2 : nếu \(\left|x-\frac{1}{3}\right|< 0\)
\(\frac{1}{3}-x< \frac{5}{3}\)
\(x>-\frac{4}{3}\)
Bài 2 :
a. \(\left(x-2\right)^2=1\)
\(\left(x-2\right)^2-1=0\)
\(\left(x-2-1\right)\left(x-2+1\right)=0\)
\(\left(x-3\right)\left(x-1\right)=0\)
\(\left[\begin{array}{nghiempt}x-3=0\\x-1=0\end{array}\right.\)
\(\left[\begin{array}{nghiempt}x=3\\x=1\end{array}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1. A = 75(42004 + 42003 +...+ 42 + 4 + 1) + 25
A = 25 . [3 . (42004 + 42003 +...+ 42 + 4 + 1) + 1]
A = 25 . (3 . 42004 + 3 . 42003 +...+ 3 . 42 + 3 . 4 + 3 + 1)
A = 25 . (3 . 42004 + 3 . 42003 +...+ 3 . 42 + 3 . 4 + 4)
A = 25 . 4 . (3 . 42003 + 3 . 42002 +...+ 3 . 4 + 3 + 1)
A =100 . (3 . 42003 + 3 . 42002 +...+ 3 . 4 + 3 + 1) \(⋮\) 100
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x : \(\left(-\frac{1}{3}\right)^3=-\frac{1}{3}\)
\(x:\frac{-1}{27}=\frac{-1}{3}\)
\(x=\frac{-1}{3}.\frac{-1}{27}\)
\(x=\frac{1}{81}\)
Vậy \(x=\frac{1}{81}\)
a) \(x:\left(-\frac{1}{3}\right)^3=-\frac{1}{3}\)
\(\Leftrightarrow x=\left(-\frac{1}{3}\right)\cdot\left(-\frac{1}{3}\right)^3\)
\(\Leftrightarrow x=\left(-\frac{1}{3}\right)^4\)
\(\Leftrightarrow x=\frac{1}{81}\)
b)\(\left(\frac{4}{5}\right)^5\cdot x=\left(\frac{4}{5}\right)^7\)
\(\Leftrightarrow x=\left(\frac{4}{5}\right)^7:\left(\frac{4}{5}\right)^5=\left(\frac{4}{5}\right)^2=\frac{16}{25}\)
c)\(\left(x+\frac{1}{2}\right)^2=\frac{1}{16}\)
\(\Leftrightarrow x+\frac{1}{2}=\frac{1}{4}\)
\(\Leftrightarrow x=-\frac{1}{4}\)
d)\(\left(3x+1\right)^3=-27\)
\(\Leftrightarrow3x+1=-3\)
\(\Leftrightarrow3x=-4\)
\(\Leftrightarrow x=-\frac{4}{3}\)
1a, 34.26.15−34.44.15=34.15.(26−44)=320.(−18)=−271034.26.15−34.44.15=34.15.(26−44)=320.(−18)=−2710
b,−√25+2√16=−√27.4=−4√27−25+216=−27.4=−427
2a, 2+x=-5
=>x=-7
b, x−1x+5=67=>7(x−1)=6(x+5)=>7x−7=6x+30=>x=37
1a, \(\frac{3}{4}.26.\frac{1}{5}-\frac{3}{4}.44.\frac{1}{5}=\frac{3}{4}.\frac{1}{5}.\left(26-44\right)=\frac{3}{20}.\left(-18\right)=\frac{-27}{10}\)
b,\(-\sqrt{25+2}\sqrt{16}=-\sqrt{27}.4=-4\sqrt{27}\)
2a, 2+x=-5
=>x=-7
b, \(\frac{x-1}{x+5}=\frac{6}{7}\\ =>7\left(x-1\right)=6\left(x+5\right)\\ =>7x-7=6x+30\\ =>x=37\)